"Auditoría financiera a la escuela de conducción del sindicato cantonal de choferes profesionales La Mana, periodo 2011" - Cañar Aguirre, Armando Johnson (2014)
The present research project is focused on the accounting process Driving School, during the period 2011; this work of Financial Audit analyzes the behavior of the accounting department of the company. To develop the theoretical framework of the research analyzed each of the variables that occur as a result of the statement of the problem, finding timely and accurate information on books, pamphlets and web pages, that my concept was necessary to meet the own technical requirements in a clear and precise wording. In terms of research methodology, methods such as inductive, deductive and analytical were used, as I believe they are the most appropriate when an audit is run. As for the techniques, it became necessary to resort to the interview, as it is the most direct method of obtaining information from the listener, to make the results of the investigation and to give complaining with the objectives was held planning activities to be performed in the audit, guided by a sequential process of the books have been a source of information and a lot of importance in the exercise, just end up concluding according to the objectives that thanks to the development of the research was able to meet, and finally to the respective recommendations for the company.